ASSESSING THE ECOLOGICAL AND MICROBIAL IMPACTS OF SHIP BALLAST WATER DISCHARGE IN GLOBAL SHIPPING - Nwaogbe, Obioma Reuben; Onyena, Amarachi Paschaline; Adeoyemi, Abidat Adebobolo; Somtochukwu, Chibuike (FUDMA JOURNAL OF SCIENCES, 2024)
The global shipping industry, responsible for 90% of world trade, plays a pivotal role in facilitating economic growth. However, its impact on marine environments, notably through pollution from ballast water discharges, poses environmental challenges. The discharge of ballast water emerges as a significant threat, introducing non-native species and pathogens into new ecosystems, leading to ecological and economic consequences. The study aims to understand the impact of these invasive species on native ecosystems, biodiversity, ecosystem function, and potential economic implications. Ten vessels from diverse regions were sampled, revealing zero total coliform counts and Escheria coli presence, indicating relatively clean ballast water. Microbiological analysis highlighted variations in heterotrophic counts across samples with zero total coliform counts and Escheria coli. The study identified the presence of pathogenic bacteria, including Bacillus sp., Vibro cholera, and Staphylococcus aureus. The study highlights the potential for the spread of invasive species through ballast water discharge, necessitating strategies to mitigate negative impacts.
Keywords: Invasive species; Ecological risk; Human health risk; Maritime transport